1994
DOI: 10.1073/pnas.91.5.1964
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy of hydrogen bond formation in aprotein-ligand binding reaction.

Abstract: Parallel measurements of the thermodynamics (free-energy, enthalpy, entropy and heat-capac change) of ligand binding to FK506 binding protein First suggested >70 years ago (1, 2) and particularly emphasized by Pauling et al. (3,4), the hydrogen bond is now recognized as an interaction of fundamental importance in determining the structures of proteins and their complexes with ligands (5). Nevertheless, conflicting views are still held on the relative energetic contributions ofhydrogen bonds and interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 29 publications
(29 reference statements)
10
71
4
Order By: Relevance
“…In a recent experiment, Eberhardt & Raines (1994) determined the relative strengths of amide-amide and amide-water hydrogen bonds. In another study of protein-ligand interaction, Connelly et al (1994) suggested that forming an interior hydrogen bond involves dehydration, which is enthalpically unfavorable.…”
Section: Hydrogen Bonding and Electrostatic Dipolar Interactionsmentioning
confidence: 98%
“…In a recent experiment, Eberhardt & Raines (1994) determined the relative strengths of amide-amide and amide-water hydrogen bonds. In another study of protein-ligand interaction, Connelly et al (1994) suggested that forming an interior hydrogen bond involves dehydration, which is enthalpically unfavorable.…”
Section: Hydrogen Bonding and Electrostatic Dipolar Interactionsmentioning
confidence: 98%
“…Yet, they can form hydrogen bonds and contribute significantly to the stability of a receptor-ligand complex. Cysteine residues d o not normally form covalent bonds between the binding species, and here they are only considered in the context of noncovalent intermolecular binding Connelly et al (1994) have noted that the mutation Y82F in the FK506 binding protein exhibits a slight destabilizing effect on the protein-ligand complex. The ligand binds through an interaction between a carbonyl group and the tyrosine hydroxyl group.…”
Section: Alcohols and Thiolsmentioning
confidence: 99%
“…For example, in the binding of the protein FKBP-12 to its macrocyclic ligands (Connelly et al 1994), residue Tyr-82 forms three hydrogen bonds to ordered water molecules in the free form of the protein, but they are replaced by a hydrogen bond to a ligand carbonyl group in the complex. Thermodynamic binding data for wild-type and mutant (Y82F) FKBP-12 collected in H 2 O and D 2 O indicated that the three water-totyrosine hydrogen bonds are (in combination) enthalpically more favorable but entropically destabilizing relative to the tyrosine-to-ligand hydrogen bond that replaces them.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%